BRUCELLOSIS SEROPOSITIVITY IN SHEEP SLAUGHTERED AT SMALL RUMINANT SLAUGHTERHOUSE IN BOGOR REGENCY - Widya Septiningtyas; Eko Sugeng Pribadi; Fachriyan Hasmi Pasaribu (Jurnal Kedokteran Hewan, 2018)
Brucellosis is among the important diseases in livestock because the disease infects multiple species of animals and causes economic loss. Brucellosis in sheep is generally caused by Brucella melitensis and/or Brucella ovis. This study aimed to detect seropositive brucellosis in sheep. Serological tests used in this study was a parallel test between Rose Bengal Test (RBT) and Complement Fixation Test (CFT). Samples were collected from 150 sheep slaughtered in small ruminant slaughterhouse, Sentul, Bogor Regency. Seropositive proportion of brucellosis in sheep based on parallel test RBT and CFT was 52% (78/150).